A Virulence Associated Siderophore Importer Reduces Antimicrobial Susceptibility of Klebsiella pneumoniae - Farzand, Robeena; Rajakumar, Kumar; Barer, Michael R.; Freestone, Primrose P. E.; Mukamolova, Galina V.; Oggioni, Marco R.; O’Hare, Helen M. (Frontiers in Microbiology, 2021)
The accessory genomes of many pathogenic bacteria include ABC transporters that scavenge metal by siderophore uptake and ABC transporters that contribute to antimicrobial resistance by multidrug efflux. There are mechanistic and recently recognised structural similarities between siderophore importer proteins and efflux pumps. Here we investigated the influence of siderophore importer YbtPQ on antimicrobial resistance of Klebsiella pneumoniae. YbtPQ is encoded in the yersiniabactin cluster in a prevalent mobile genetic element ICEKp, and is also common in pathogenicity islands of Escherichia coli and Yersinia species, where yersiniabactin enhances virulence. Deletion of ICEKp increased the susceptibility of K. pneumoniae to all antimicrobials tested. The mechanism was dependent on the yersiniabactin importer YbtPQ and may involve antimicrobial efflux, since it was affected by the inhibitor reserpine. The element ICEKp is naturally highly mobile, indeed the accessory genome of K. pneumoniae is recognised as a reservoir of genes for the emergence of hospital outbreak strains and for transfer to other Gram-negative pathogens. Introduction of ICEKp, or a plasmid encoding YbtPQ, to E. coli decreased its susceptibility to a broad range of antimicrobials. Thus a confirmed siderophore importer, on a rapidly evolving and highly mobile element capable of interspecies transfer, may have a secondary function exporting antimicrobials.